2015
DOI: 10.1186/s12967-015-0729-0
|View full text |Cite
|
Sign up to set email alerts
|

Value of the prognostic nutritional index and weight loss in predicting metastasis and long-term mortality in nasopharyngeal carcinoma

Abstract: BackgroundTo evaluate the influence of the progonistic nutritional index (PNI) and weight loss on metastasis and long-term mortality in nasopharyngeal carcinoma (NPC).MethodsWe retrospectively reviewed 694 newly diagnosed patients with non-disseminated, biopsy-proven NPC. Survival analysis was used to evaluate the predictive value of PNI and weight loss.ResultsMultivariate analysis demonstrated that a low pre-therapy PNI (< 55.0) was an independent predictor of poor overall survival (OS) (P = 0.012), distant m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
71
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 30 publications
14
71
0
Order By: Relevance
“…However, our study failed to identify a cut-off value for LRRFS, which may be explained by the high loco-regional control rate (>90%) in the era of IMRT. These results were similar to the previous study (Du et al 2015). Although radiotherapy combined with chemotherapy has been widely accepted as the standard treatment modality for advanced NPC, the optimal chemotherapy regimen for this disease has yet to be defined.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, our study failed to identify a cut-off value for LRRFS, which may be explained by the high loco-regional control rate (>90%) in the era of IMRT. These results were similar to the previous study (Du et al 2015). Although radiotherapy combined with chemotherapy has been widely accepted as the standard treatment modality for advanced NPC, the optimal chemotherapy regimen for this disease has yet to be defined.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the PNI is considered a good index that reflects both the nutritional and immune status of the host (Ikeya et al 2015). Although the PNI was originally proposed by Onodera to assess postoperative complications of patients who underwent gastrointestinal surgery (Onodera et al 1984), increasing evidence has shown that the PNI is closely related to long-term outcomes and represents an independent prognostic factor for the survival of patients with various cancers (Ikeya et al 2015;Goodwin and Torres 1984;Hong et al 2015;Hofbauer et al 2015;Jiang et al 2014;Du et al 2015). In the current study, we conducted a retrospective study to investigate the significance of the PNI in predicting the prognosis of NPC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective studies demonstrated that weight loss is the strongest independent predictor of survival in patients with HNC 21,24. Recently, two reports from China indicated that NPC patients with high weight loss during treatment have significantly poor survival 25,26. Therefore, it is necessary to maintain weight in cancer patients during the treatment period.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 The prognostic nutritional index (PNI), which was first designed by Buzby et al, 7 was calculated based on the serum albumin concentration and lymphocyte count in the peripheral blood. 8 Recently, emerging evidence has demonstrated the prognostic value of PNI in different types of malignant tumors, including hepatocellular carcinoma, 9 nasopharyngeal carcinoma, 10 and colorectal cancer. 11 Moreover, Sun et al 12 have performed a pooled analysis to estimate the prognostic value of PNI in cancer.…”
Section: Introductionmentioning
confidence: 99%